2018
DOI: 10.4236/ojog.2018.811099
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Bishop Score and Success of Induction of Labour in Federal Teaching Hospital, Abakaliki, Ebonyi State

Abstract: Background: The ripeness of the cervix is of critical importance to the probability of successful labour induction. Aim: To determine the relationship between successful induction of labour and Bishop score. Materials and Methods: A retrospective study of all obstetric patients who had induction of labour between January 1 st 2012 and December 31st 2015 was done in Federal Teaching Hospital Abakaliki. The information obtained from patients' case notes was analyzed using descriptive and inferential statistics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
0
8
0
2
Order By: Relevance
“…The Calder Modification replaces cervical effacement with cervical length with a total score of 12 (Table 2) [31,32]. In a retrospective study [33] done recently to closely look at the relationship between bishop score and successful induction, a higher bishop score (8-10) at the beginning of IOL is directly proportional to the higher rates of successful IOL compared with bishop score between 6 and 7. There is recent evidence to show that the cervical length assessment by transvaginal ultrasound appear to be superior to the bishop score, however this is not a routine practice [34].…”
Section: Preinduction Cervical Statementioning
confidence: 99%
“…The Calder Modification replaces cervical effacement with cervical length with a total score of 12 (Table 2) [31,32]. In a retrospective study [33] done recently to closely look at the relationship between bishop score and successful induction, a higher bishop score (8-10) at the beginning of IOL is directly proportional to the higher rates of successful IOL compared with bishop score between 6 and 7. There is recent evidence to show that the cervical length assessment by transvaginal ultrasound appear to be superior to the bishop score, however this is not a routine practice [34].…”
Section: Preinduction Cervical Statementioning
confidence: 99%
“…Bishop score has proven to be a good predictor of successful induction in many studies. [12,13] We noticed that women with a Bishop score >6 had a better success rate compared with women with a score <5 (p=0.272). Although Bishop score is an important predictor of the success of induction, the systematic review done by Kolkman et al [14] concluded that Bishop score, individually, was a poor predictor of the outcomes of induced labour.…”
Section: Discussionmentioning
confidence: 81%
“…They are assisted by trained midwives. Parturients in labor are admitted in the labor ward when the cervical dilatation is 4 cm and above, while those for induction of labor are admitted when the Bishop score 13 is 6 and above. They were managed with individualized partograph according to the departmental protocol.…”
Section: Methodsmentioning
confidence: 99%